Pola Sebaran Spasial Stunting di Kabupaten Lampung Selatan dengan Pendekatan Autokorelasi Spasial - Wayan Wardana; Khursatul Munibah; Yayuk Farida Baliwati (Journal of Regional and Rural Development Planning (Jurnal Perencanaan Pembangunan Wilayah dan Perdesaan), 2023)
Stunting is a condition in toddlers who experience failure to thrive due to chronic malnutrition which causes children to be shorter than their cohort. The Indonesian Ministry of Health's Basic Health Research in 2018 reported that the prevalence of stunting in the South Lampung Regency was above the WHO standard of 20%, although it decreased from 43.01% in 2013 to 29.08% in 2018. This study aims to identify spatial distribution pattern of stunting prevalence in the South Lampung Regency. The methods included Moran's Index, Moran's Scatterplot, Local Indicator of Spatial Association (LISA) and correlation analysis. The results showed that there was a spatial autocorrelation to the prevalence of stunting in South Lampung Regency with the spatial distribution pattern being clustered. The grouping of areas in the high-high (HH) cluster is mostly located in villages in Kalianda District with one of the contributing factors being the joint use of water from inappropriate sources. Clean water provision is expected to reduce stunting prevalence in the South Lampung Regency.